Cycling Intensity Effect on Running Plus Cycling Performance among Triathletes - Vivan, Lavínia; dos Anjos, Vinicius Ribeiro; Engelke, Paulo; de Lira, Claudio Andre Barbosa; Vancini, Rodrigo Luiz; Weiss, Katja; Knechtle, Beat; Andrade, Marília Santos (International Journal of Sports Medicine, 2024)
Running performance is crucial for triathlon performance. However, the prior bout of cycling may affect the running split time. This study compared the triathletes’ cycling plus running (C+R) time, when cycling was performed at three different intensities and running was maximal. A total of 38 athletes (21 males and 17 females) were included. Body composition, maximal oxygen uptake, and functional threshold power (FTP) was evaluated. The participants visited the laboratory three times to cycle 20 km at 80%, 85%, or 90% FTP (in randomized order) and run 5 km as fast as possible. Males ran faster after cycling at 80% FTP than after cycling at 90% FTP (mean difference=35.1 s; CI% 2.2, 68.1 s; p=0.035). The C+R time was faster when cycling at 90% FTP than at 80% FTP (mean difference=57.7 s; CI% 26.1, 89.3 s; p<0.001). For females, no significant difference was observed in the running time after cycling at 80%, 85%, or 90% FTP. The C+R time was faster when cycling at 90% FTP than at 80% FTP (mean difference=80.9 s; CI% 29.7, 132.1 s; p=0.002). In conclusion, to optimize triathlon performance, male and female athletes should cycle at a minimum of 90% FTP.
Keywords: cycling time; running time; performance; triathlon; functional threshold power